Benign macrocystic serous cystadenoma of the pancreas - Selma Erdogan Duzcu; Nur Tunc (Wolters Kluwer Medknow Publications, 2021)
Serous cystadenoma is a rare benign cystic lesion of pancreas. They are mostly known as benign cystic tumors of pancreas but malign transformation as serous cystadenocarcinoma is also reported. It is more commonly observed in women with the mean age of onset is 62 years. The majority of patients present nonspecific symptoms such as abdominal pain, weight loss, nausea, vomiting, fever, and melena. One-third of the patients are asymptomatic. A 60-year-old woman presents with abdominal pain and nausea for 1 month was admitted. Physical and laboratory findings were normal. Abdomen computed tomography scan confirmed a large number of millimetric cysts of 45 × 47 × 50 mm in size at the head of the pancreas. Due to patient's symptoms and mass effect, Whipple procedure was performed. In the gross examination, a nodular area of 5 × 5 × 4 cm was observed in the head of the pancreas. The microscopic examination of the material revealed cystic structures with fibrous stroma dotted with single layered cuboidal epithelium in the pancreatic tissue. The pathology report confirmed benign macrocystic serous cystadenoma. Serous cystadenomas are rare benign cystic lesions of the pancreas. Although they are benign lesions, it is crucial to differentiate them from other cystic lesions of the pancreas and malignant serous cystadenocarcinomas.